Sistem Pakar Perilaku Buruk Psikologis pada Anak dengan Metode Forward Chaining - Doddy Satrya Perbawa, Wawan Laksito, Didik Nugroho (STMIK Sinar Nusantara, 2012)
Expert systems solve the problem of bad behavior in children psikoligis can help a person to cope with bad behavior in children based on psychological knowledge of symptoms and complaints of the patients felt that the patient is a parent of the child, so as to take preventive and early treatment that will not cause the child to experience psychological disorders. The method of data collection that is used by the writer is observation method or of observe directly the behavior who experiences many disturbances on bad behavioural psychologic on children, interview methode and references (take from book and literature). This research contains bad behavior systems program in which the child psychologists and experts there to increase knowledge about the psychology of bad behavior in children symptoms or signs and how to overcome from psychological disorders in bad behavior. Keywords: children healthiness, psychologic